The Role of Human Milk Oligosaccharides and Probiotics on the Neonatal Microbiome and Risk of Necrotizing Enterocolitis: A Narrative Review - Nolan, Lila S. (Nutrients, 2020)
Preterm infants are a vulnerable population at risk of intestinal dysbiosis. The newborn microbiome is dominated by Bifidobacterium species, though abnormal microbial colonization can occur by exogenous factors such as mode of delivery, formula feeding, and exposure to antibiotics. Therefore, preterm infants are predisposed to sepsis and necrotizing enterocolitis (NEC), a fatal gastrointestinal disorder, due to an impaired intestinal barrier, immature immunity, and a dysbiotic gut microbiome. Properties of human milk serve as protection in the prevention of NEC. Human milk oligosaccharides (HMOs) and the microbiome of breast milk are immunomodulatory components that provide intestinal homeostasis through regulation of the microbiome and protection of the intestinal barrier. Enteral probiotic supplements have been trialed to evaluate their impact on establishing intestinal homeostasis. Here, we review the protective role of HMOs, probiotics, and synbiotic combinations in protecting a vulnerable population from the pathogenic features associated with necrotizing enterocolitis.